Service Learning in Gurindam Twelve Learning at The Indera Perkasa Customary Center of Penyengat Island, Indonesia - Satriadi Satriadi; Nefrida Nefrida; Via Riani; Risaldi Risaldi; Syah Ramadhani Siregar; Deffran Deffran (Jurnal Kemitraan Masyarakat, 2025)
This community service program aims to implement a service learning model in Gurindam Dua Belas learning at the Indera Perkasa Traditional Hall, Penyengat Island, as an effort to strengthen cultural literacy and character education based on local wisdom. The activity was implemented through the Real Work Lecture (KKN) program with a participatory approach involving traditional leaders, traditional hall managers, and students. The service stages included planning with partners, preparing learning materials and scenarios, implementing reading-recitation sessions and value discussions, as well as joint evaluation and reflection. The results of the activity showed an increase in participant involvement in understanding, reciting, and interpreting Gurindam Dua Belas, strengthening the function of the Indera Perkasa Traditional Hall as a cultural learning space, and enriching students' pedagogical experience in designing local wisdom-based learning. The main limitations of this program were the short duration of implementation, limited participant reach, and less than optimal use of digital media.